Pengembangan Gerak Dan Lagu Anak Berbasis Tri Kaya Parisudha Sebagai Media Pengenalan Karakter Hindu Pada Anak Usia Dini - Kamalia Jaya, Praptika; Marsono, Marsono; Sindu Putra, Ida Bagus Komang; Suardika, I Komang; Septiari Dewi, Putu Ayu; Chandra Suari, Ni Wayan Gita (Jayapangus Press, 2025)
Children’s movement and song activities are a form of play that have always been an integral part of learning in early childhood education. In early childhood education institutions and kindergartens with a Hindu nuance, religious education often employs audiovisual media that feature movements and songs based on themes derived from Hindu teachings. One of the most frequently introduced themes is the concept of Tri Kaya Parisudha due to its relevance to the daily behaviors of children. The objective of this study is to develop Hindu-themed movements and songs centered on the Tri Kaya Parisuda concept. The research method used is Research and Development (R&D). The development process followed the ADDIE model. Children aged 5–6 years from Tunas Wangi Hindu State Kindergarten in Bone Village were selected as the study sample. Data from expert validation and field validation of the product were analyzed using both qualitative and quantitative methods. Qualitative analysis employed the Content Validity Ratio (CVR) formula by Lawshe. The developed movement and song successfully reflected the values of the Tri Kaya Parisudha concept. All validators agreed that the movements and songs used are appropriate and relevant to Hindu character values, as evidenced by a CVR score of 1.0 for this aspect. This indicates that this learning media is highly essential for introducing Hindu character concepts to early childhood learners.